Amoebae: beyond pathogens- exploring their benefits and future potential - Suman Kalyan Dinda; Shreyasee Hazra; Anwesha De; Annurima Datta; Lipika Das; Santanu Pattanayak; Kishor Kumar; Manash Deep Dey; Arnab Basu; Dipak Manna (Frontiers in Cellular and Infection Microbiology)
Amoebae, fascinatingly diverse protists, showcase a dual nature that positions them as both friends and foes in our world. These organisms, defined by their distinctive pseudopodia, span a spectrum from harmful to helpful. On the darker side, species like Entamoeba histolytica pose serious health risks, causing intestinal and liver diseases, while the infamous “brain-eating” Naegleria fowleri leads to fatal primary amoebic meningoencephalitis (PAM), with a daunting 97% mortality rate. Other free-living amoebae, including Acanthamoeba castellanii and Balamuthia mandrillaris, also threaten the human central nervous system. Yet, beyond these dangers, amoebae play critical ecological roles. They function as nature’s recyclers, decomposing organic material and nourishing aquatic ecosystems, while also serving as food for various organisms. Moreover, certain amoebae help control plant pathogens and offer insight into human disease, proving valuable as model organisms in biomedical research. This review sheds light on the complex, multifaceted world of amoebae, highlighting their dual role as pathogens and as key contributors to vital ecological processes, as well as their significant impact on research and their promising potential for enhancing human well-being.